Nalar Gender Calon Guru Agama - Muhammad Ihsan Siregar; Marhumah; Zulfa Khairiah Ali (4, 2026)
Gender-related hadiths remain a significant issue in Islamic education, as they are often interpreted textually, leading to perspectives that may not adequately address contemporary social realities. This study aims to examine Islamic Education (PAI) students’ understanding of gender-related hadiths, explore their gender reasoning, and analyze their readiness to contextualize these hadiths within school settings. This research employed a qualitative case study approach. Data were collected through in-depth interviews, observations, and document analysis, and were analyzed using the Miles, Huberman, and Saldaña interactive model. The findings reveal that most participants interpret gender-related hadiths through a historical-contextual approach by considering the socio-historical background and moral objectives of the texts. Their gender reasoning tends to emphasize equality of human dignity, justice, and complementary roles between men and women. Furthermore, the participants demonstrated readiness to contextualize gender-related hadiths through participatory learning strategies, historical-contextual approaches, critical literacy development, and the ability to respond to students’ questions in an argumentative and balanced manner. The novelty of this study lies in integrating the analysis of hadith understanding, gender reasoning, and the pedagogical readiness of prospective Islamic education teachers within a single analytical framework. Abstrak Hadis-hadis gender menjadi isu penting dalam pendidikan Islam karena sering dipahami secara tekstual sehingga berpotensi melahirkan pandangan yang kurang relevan dengan realitas sosial kontemporer. Penelitian ini bertujuan menganalisis pemahaman mahasiswa Pendidikan Agama Islam (PAI) terhadap hadis-hadis gender, mengkaji nalar gender yang mereka bangun, serta menelaah kesiapan mereka dalam mengontekstualisasikan hadis-hadis gender di sekolah. Penelitian menggunakan pendekatan kualitatif dengan jenis studi kasus. Data diperoleh melalui wawancara mendalam, observasi, dan dokumentasi, kemudian dianalisis menggunakan model Miles, Huberman, dan Saldaña. Hasil penelitian menunjukkan bahwa mayoritas mahasiswa memahami hadis gender secara historis-kontekstual dengan mempertimbangkan latar belakang kemunculan hadis dan pesan moral yang dikandungnya. Nalar gender mahasiswa cenderung mengarah pada prinsip kesetaraan martabat, keadilan, dan komplementaritas antara laki-laki dan perempuan. Selain itu, mahasiswa menunjukkan kesiapan mengontekstualisasikan hadis gender melalui strategi pembelajaran partisipatif, pendekatan historis-kontekstual, pengembangan literasi kritis, serta kemampuan merespons pertanyaan siswa secara argumentatif. Kebaruan penelitian ini terletak pada integrasi analisis pemahaman hadis gender, nalar gender, dan kesiapan pedagogis calon guru agama dalam satu kerangka kajian.